K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

20 tháng 10 2021

\(2x^3+16\)

\(=2\left(x^3+8\right)\)

\(=2\left(x+2\right)\left(x^2-2x+4\right)\)

HQ
Hà Quang Minh
Giáo viên
24 tháng 9 2023

\(16\cdot\left(2x+3\right)^2-9\cdot\left(5x-2\right)^2\\ =\left(8x+12\right)^2-\left(15x-6\right)^2\\ =\left(8x+12-15x+6\right)\left(8x+12+15x-6\right)\\ =\left(-7x+18\right)\left(23x+6\right)\)

7 tháng 8 2023

a) \(x^4+8x+63\)

\(=x^4+4x^3+9x^2-4x^3-16x^2-36x+7x^2+28x+63\)

\(=x^2\left(x^2+4x+9\right)-4x\left(x^2+4x+9\right)+7\left(x^2+4x+9\right)\)

\(=\left(x^2+4x+9\right)\left(x^2-4x+7\right)\)

7 tháng 8 2023

c) \(\left(x^2+2x+7\right)+\left(x^2-2x+4\right)\left(x^2+2x+3\right)\left(1\right)\)

Ta có : \(x^3-8=\left(x-2\right)\left(x^2+2x+4\right)\)

\(\Rightarrow x^2+2x+4=\dfrac{x^3-8}{x-2}\)

\(\left(1\right)\Rightarrow\left[\left(\dfrac{x^3-8}{x-2}+3\right)\right]+\left(x^2-2x+4\right)\left[\left(\dfrac{x^3-8}{x-2}-1\right)\right]\)

\(=\left[\left(\dfrac{x^3-3x-14}{x-2}\right)\right]+\left(x^2-2x+4\right)\left[\left(\dfrac{x^3-2x-5}{x-2}\right)\right]\)

\(=\dfrac{1}{x-2}\left[x^3-3x-14+\left(x^2-2x+4\right)\left(x^3-2x-5\right)\right]\)

18 tháng 10 2021

\(x^2+2x+1-16=\left(x+1\right)^2-4^2=\left(x+1-4\right).\left(x+1+4\right)=\left(x-3\right).\left(x+5\right)\)

18 tháng 10 2021

\(x^2+2x+1-16=\left(x^2+2x+1\right)-4^2=\left(x+1\right)^2-4^2=\left(x+1-4\right)\left(x+1+4\right)=\left(x-3\right)\left(x+5\right)\)

a: \(x^3-9x^2+6x+16\)

\(=x^3-8x^2-x^2+8x-2x+16\)

\(=x^2\left(x-8\right)-x\left(x-8\right)-2\left(x-8\right)\)

\(=\left(x-8\right)\left(x^2-x-2\right)\)

\(=\left(x-8\right)\left(x-2\right)\left(x+1\right)\)

b: \(x^3-x^2-x-2\)

\(=x^3-2x^2+x^2-2x+x-2\)

\(=x^2\left(x-2\right)+x\left(x-2\right)+\left(x-2\right)\)

\(=\left(x-2\right)\cdot\left(x^2+x+1\right)\)

c: \(x^3+x^2-x+2\)

\(=x^3+2x^2-x^2-2x+x+2\)

\(=x^2\left(x+2\right)-x\left(x+2\right)+\left(x+2\right)\)

\(=\left(x+2\right)\left(x^2-x+1\right)\)

d: \(x^3-6x^2-x+30\)

\(=x^3+2x^2-8x^2-16x+15x+30\)

\(=x^2\left(x+2\right)-8x\left(x+2\right)+15\left(x+2\right)\)

\(=\left(x+2\right)\left(x^2-8x+15\right)\)

\(=\left(x+2\right)\left(x-3\right)\left(x-5\right)\)

e: Sửa đề: \(x^3-7x-6\)

\(=x^3-x-6x-6\)

\(=x\left(x^2-1\right)-6\left(x+1\right)\)

\(=x\left(x-1\right)\left(x+1\right)-6\left(x+1\right)\)

\(=\left(x+1\right)\left(x^2-x-6\right)\)

\(=\left(x+1\right)\left(x-3\right)\left(x+2\right)\)

f: \(27x^3-27x^2+18x-4\)

\(=27x^3-9x^2-18x^2+6x+12x-4\)

\(=9x^2\left(3x-1\right)-6x\left(3x-1\right)+4\left(3x-1\right)\)

\(=\left(3x-1\right)\left(9x^2-6x+4\right)\)

g: \(2x^3-x^2+5x+3\)

\(=2x^3+x^2-2x^2-x+6x+3\)

\(=x^2\left(2x+1\right)-x\left(2x+1\right)+3\left(2x+1\right)\)

\(=\left(2x+1\right)\left(x^2-x+3\right)\)

h: \(\left(x^2-3\right)^2+16\)

\(=x^4-6x^2+9+16\)

\(=x^4-6x^2+25\)

\(=x^4+10x^2+25-16x^2\)

\(=\left(x^2+5\right)^2-\left(4x\right)^2\)

\(=\left(x^2+5+4x\right)\left(x^2+5-4x\right)\)

 

14 tháng 10 2021

c: \(x^2-4+3\left(x-2\right)^2\)

\(=\left(x-2\right)\left(x+2\right)+\left(x-2\right)\left(3x-6\right)\)

\(=\left(x-2\right)\left(x+2+3x-6\right)\)

\(=\left(4x-4\right)\left(x-2\right)\)

\(=4\left(x-1\right)\left(x-2\right)\)

29 tháng 8 2021

c) \(16-x^2+2xy-y^2=\left(4-x+y\right)\left(4+x-y\right)\)

d) \(\left(x-1\right)^2-4\left(2x-3\right)^2=\left(5-3x\right)\left(5x-7\right)\)

e) \(x^3-3x^2+3x-1=\left(x-1\right)^3\)

e) \(x^2-7=\left(x-\sqrt{7}\right)\left(x+\sqrt{7}\right)\)

24 tháng 11 2021

\(1,=4x^2-1\\ 2,=\left(x-4\right)^2-9y^2=\left(x-3y-4\right)\left(x+3y-4\right)\)

24 tháng 11 2021

1)\(\left(2x+1\right)\left(2x-1\right)=\left(2x\right)^2-1^2=4x^2-1\)

2)\(x^2-8x-9y^2+16=\left(x^2-8x+16\right)-9y^2=\left(x^2-8x+4^2\right)-\left(3y\right)^2=\left(x-4\right)^2-\left(3y\right)^2=\left[\left(x-4\right)-3y\right]\left[\left(x-4\right)+3y\right]=\left(x-4-3y\right)\left(x-4+3y\right)\)

9 tháng 11 2018

\(16\left(2x+3\right)^2-9\left(5x-2\right)^2\)

\(=\left[4\left(2x+3\right)\right]^2-\left[3\left(5x-2\right)\right]^2\)

\(=\left[4\left(2x+3\right)-3\left(5x-2\right)\right]\left[4\left(2x+3\right)+3\left(5x-2\right)\right]\)

\(=\left(-7x+18\right)\left(23x+6\right)\)

6 tháng 12 2019

\(b.=4\left(x^2+4x+4\right)\)

\(=4\left(x+2\right)^2\)

Học tốt

6 tháng 12 2019

\(x^3-2x^2+x-xy^2\)

\(=x\left(x^2-2x+1-y^2\right)\)

\(=x\left[\left(x-1\right)^2-y^2\right]\)

\(=x\left(x-1-y\right)\left(x-1+y\right)\)

Câu 1:

\(=x^2-\left(y-4\right)^2\)

\(=\left(x-y+4\right)\cdot\left(x+y-4\right)\)